The genius and the goddess: Lampedusa’s La sirena - Fairservice, David (Spunti e Ricerche, 2016)
Gioacchino Lanza Tomasi tells us that Lampedusa was "specialmente fiero" of his story about the professor and the Siren, which was first published as Lighea, the title given by Lampedusa’s widow, and which has been republished, with minor textual corrections and some pages of an earlier draft, as La Sirena. Since the publication of his ’lectures’, especially those on English literature, it has become even more apparent that Lampedusa had a prodigious, truly ’monstrous’ knowledge of half a dozen literatures. Given the decades he had devoted to reading and the late age at which he came to writing, it is not surprising that the comparatively little that Lampedusa wrote is, to use a metaphor congenial to the writer himself, an intricate tissue of allusions.